The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0103-50532003000400023
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic voltammetric behaviour of dimensionally stable anodes in the presence of C1 - C3 aldehydes

Abstract: Este trabalho descreve o estudo voltamétrico de três aldeídos alifáticos: formaldeído, acetaldeído e propionaldeído sobre ânodos do tipo Dimensionalmente Estáveis (ADE  ). Eletrodos com composição Ti/Ru 0.3 M 0.7 O 2 (onde M = Ti ou Sn) foram utilizados em solução de 0.5 mol dm -3 H 2 SO 4 usando uma célula do tipo filtro-prensa. Ambos os eletrodos apresentam um comportamento típico dos ADE  frente a oxidação de formaldeído. Porém, para acetaldeído e propionaldeído, um desvio do padrão é observado na forma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Similar results have also been found by Hu [20]. However, at low temperature we found (101) is preferred, which is different to Hu's results.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results have also been found by Hu [20]. However, at low temperature we found (101) is preferred, which is different to Hu's results.…”
Section: Resultssupporting
confidence: 70%
“…Combining this with temperature dependent preferable crystallite orientation, (101) IrO 2 crystallites formed at either low or moderate temperature might be less stressed and/or less influenced by dissolved Ta atoms. It has been reported that (101) rutile IrO 2 displays better catalytic activity since the length of the bond for Ir-O is shorter for (101) than the other facets [20]. It also has been reported that the stability of (101) IrO 2 crystallites for OER is better than (110) IrO 2 [11].…”
Section: Resultsmentioning
confidence: 99%
“…The displayed broad peaks between the OER and the hydrogen evolution correspond to oxidation state transitions of noble metals (Ir 3+ /Ir 4+ in this case). 30 It is clear that the peak current decreases with increasing calcination temperature and moves the onset potential of OER toward more positive potentials. Since the oxide compositions are almost equal, an apparent change in voltammetric response and OER onset potential may be attributed to the surface morphology and a change in active surface area.…”
Section: Resultsmentioning
confidence: 95%
“…3,8,9 This is exemplified by an increase in the value of the anodic charge in the potential region above 0.5 V vs. MSE and an increase in the current associated with the oxygen evolution reaction (OER). The effect of increasing the concentration of formaldehyde is manifested by a quasi-linear increase in the magnitude of q fN for all electrodes.…”
Section: Cyclic Voltammetry In Presence Of Formaldehydementioning
confidence: 99%
“…3,8 Two different concentrations were investigated, one in the higher concentration domain (0.10 mol dm -3 ) and the other in the lower range (0.01 mol dm -3 ), in order to compare the results obtained in the previous section.…”
Section: Galvanostatic Electrolysismentioning
confidence: 99%